Porozumění českým a francouzským sémantickým gestům - Romana Suchá (AntropoWebzin, 2013)
This paper presents the results of a research project examining intercultural variations in the comprehension of Czech and French emblematic gestures. Four focus groups were asked to formulate their understanding of twenty selected gestures: ten French emblematic gestures and ten Czech gestures. The groups included: Czechs cooperating with French in the Czech Republic (Ca), French cooperating with Czechs in the Czech Republic (Fa), Czechs without any previous experience of working jointly with the French (Cb) and French lacking such contact with Czechs (Fb). Each group consisted of 20 respondents. The researcher demonstrated each of the twenty gestures and the respondents were asked to interpret their understanding of these in their own words. The responses were then coded as either ‘understood’ or ‘not understood’. The Chi-square test was applied to the analysis of the data collected to establish the significance of the results obtained. The research confirmed a positive influence of mutual contact by group Fa, as it was able to demonstrate a better understanding of Czech emblematic gestures compared to group Fb. Similarly, group Ca reaffirmed a better understanding of French gestures compared to group Cb. In the set, four gestures were understood by both the French and Czech sub-groups and no interactional cultural influence was established.